Message of Da’wa in Ruqyah on Covid-19 Treatment: Speech Act Analysis of Prof Zahro’s Broadcast on Youtube 'Ain Disease - Farida, Nur; Huda, Sokhi; Bachtiar, M. Anis (Proceedings of International Conference on Da'wa and Communication, 2022)
This study reveals the meaning of the message of da’wa from the method of treating `Ayn disease in Covid 19 in the ruqyah method according to Prof. Zahro. This study uses a qualitative textual approach with sociolinguistic analysis of Austin and Searle’s speech acts. The results of the study show a message of belief in strengthening faith and endeavor to Allah SWT. The substance is that religion and science go hand in hand, with the support of the opinions of Imam al-Ghazali and scientists Einstein and Alexis. Religion can function as a method of spiritual, inner, and belief treatment such as ruqyah or prayer and `Ayn. While science can function as a method of physical treatment in medical matters, such as Covid 19 and others. The cure for all medicines comes from a positive belief in the heart and soul, that all diseases can certainly be cured with the certainty of effort to achieve healing.